2004
DOI: 10.1158/0008-5472.can-03-0560
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Early Growth Response-1 and Its Role in Uterine Leiomyoma Growth

Abstract: Expression of early growth response (Egr)-1, a transcriptional factor implicated in growth regulation, is suppressed in several malignant tumors. The present study investigated the expression of Egr-1 and related genes in uterine leiomyoma and normal myometrium to determine possible contributions of Egr-1 to neoplastic growth in leiomyoma cells. Levels of Egr-1 transcripts were decreased in all leiomyomas (n ‫؍‬ 20) to approximately 10% of levels in corresponding myometrium, where basal expression was high. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…Interestingly, a similar pattern of downregulation of immediate-early SRF targets was also verified in FH-deficient leiomyomas as well as in sporadic leiomyomas. Decreased expression levels of FOS and JUNB in leiomyomas were previously reported (Hoffman et al, 2004;Shozu et al, 2004;Arslan et al, 2005). Although it remains unclear whether or how SRF Ser-103 phosphorylation contributes to activation of SRF target genes, our data strongly suggest that FH-induced alterations in signaling result in reduced FOS-JUNB network expression.…”
Section: Srf-fos-junb Pathway In Myomas N Raimundo Et Alsupporting
confidence: 77%
“…Interestingly, a similar pattern of downregulation of immediate-early SRF targets was also verified in FH-deficient leiomyomas as well as in sporadic leiomyomas. Decreased expression levels of FOS and JUNB in leiomyomas were previously reported (Hoffman et al, 2004;Shozu et al, 2004;Arslan et al, 2005). Although it remains unclear whether or how SRF Ser-103 phosphorylation contributes to activation of SRF target genes, our data strongly suggest that FH-induced alterations in signaling result in reduced FOS-JUNB network expression.…”
Section: Srf-fos-junb Pathway In Myomas N Raimundo Et Alsupporting
confidence: 77%
“…Since the discovery of siRNAs as the key mediator of RNA-induced gene silencing, RNAi has rapidly evolved to become a tool for gene regulation in mammals (26) and has been applied since then to inhibit the expression of a wide variety of target genes. One of them, the Egr-1 gene expressing a transcription factor with important functions in the regulation of growth and differentiation, is involved in the transformed phenotype of several cancer types (34,(39)(40)(41)(42)(43)(44)(45).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that Egr-1 can suppress human tumor cell growth and growing evidence suggests that Egr-1 functions as a tumor suppressor gene (37). The role of Egr-1 has been demonstrated in several kind of tumor cells, including human fibrosarcoma, glioblastoma and breast cancer cell lines (37,38), glioblastoma (39), neuroblastoma (10), hepatoma (40), esophageal cancer (41) and leiomyoma (42). In addition, Egr-1 can regulate the coordinated expression of a set of genes, including PTEN ( One day after plating, the cells were transfected with lipofectamine plus siRNA-Egr-1 or scrambled siRNA for 5 h, after which the medium was replaced with fresh medium containing 1 μM or 5 μM Cpt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were treated as described for panels A and B and then subjected to an assay to detect expression of Egr-1 and the internal control GAPDH glyc(glyceraldehyde-3-phosphate dehydrogenase). The details of the primers and PCR conditions used were described previously (47). (D) EBV-negative B-lymphoid cell lines BJAB and Akata were transfected with the vector plasmid (V) or the Zta-expressing plasmid (Z) by electroporation following our previously described protocol (11).…”
Section: Fig 2 Zta Induces Egr-1 Expression (A) Ebv-negative Npc-tmentioning
confidence: 99%